Boyhoods : rethinking masculinities - Corbett, Ken (Yale University Press, 2009)
Familiar and expected gender patterns help us to understand boys but often constrict our understanding of any given boy. In "Boy Hoods," Corbett seeks to release boys from the grip of expectation as Mary Pipher did for girls in "Reviving Ophelia."